Greek military service in the ancient Near East, 401-330 BCE - Rop, Jeffrey (Cambridge University Press, 2019)
This is the first monograph dedicated to the history of Greek military service for the Achaemenid Persian Empire and the Kingdom of Egypt from the rebellion of Cyrus the Younger to the conquests of Alexander the Great. Through careful analysis of the political contexts of their recruitment and detailed reconstructions of their performances as soldiers and generals on the battlefield, Jeffrey Rop overturns the traditional view that the Greeks who fought in the Near East were mercenaries hired for their superior military skills as heavily armored hoplites. The presence of unprecedented numbers of Greek infantry in the armies of Persia and Egypt is not evidence that the levies of these states were militarily inferior or deficient, but a clear sign of unprecedented foreign political influence among the most powerful leaders and cities of Greece for much of the fourth century.